Reply to the comment by Osipov et al. to "Carbon structure in nanodiamonds elucidated from Raman Spectroscopy". (August 2018) - Korepanov, Vitaly I.; Osawa, Eiji; Lednev, Igor K.; Hamaguchi, Hiro-o
Abstract: Osipov and co-authors [1] commented on our recent paper "Carbon structure in nanodiamonds elucidated from Raman Spectroscopy" [2]. We wish to reply to their comments to further clarify the issues.